IMPLEMENTASI DIPLOMASI EKONOMI INDONESIA DALAM MENINGKATKAN EKSPOR KOPI KE RUSIA PADA 2019-2021 - Rahmaini, Rahmaini; Pertiwi, Setya Ambar; Mahesa, Dirga Dwi (Moestopo Journal of International Relations (MJIR), 2025)
This thesis aims to analyze the implementation of Indonesia's economic diplomacy in increasing coffee exports to Russia in the period 2019 to 2021. The method used in this research is a qualitative explanatory method. Data collection techniques, namely library research through books, journals, scientific reports and internet sites and interviews. The theories or concepts researchers used are economic diplomacy, international trade, gastrodiplomacy, competitive advantage. This research attempts to explain the Indonesian government's efforts to increase its coffee exports to Russia by using economic diplomacy instruments. The researcher concludes that the Indonesian government has made several efforts in order to promote coffee from Indonesia in the Russian market and it can be said that Indonesia's international trade potential through coffee is promising, but behind all that there are several obstacles that are still being encountered which cause the less than optimal export of coffee from Indonesia to Russia.